Foreign Direct Investment in India after New Policy in 1991: Impact of New Policy on Foreign Direct Investment in India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
FDI may be defined as an investment involving a lasting interest and control by an investor who is a resident of another economy, other than that of the host economy. In the simple sense, FDI implied that the investor has a significant degree of influence on the management. Foreign Direct Investments are investments made by residents of one economy with the objective of establishing a lasting interest in a company located in another economy (host economy).